39 Impaired autonomic function after incomplete cardiac revascularisation. (30th September 2020) - Armstrong, R; Wheen, P; Cosgrave, J; Kenny, RA; Maree, A
Abstract : Introduction: Incomplete cardiac revascularisation (ICR) assessed by residual SYNTAX score (rSs) is associated with increased 5 year mortality. Furthermore, in the general population our group has demonstrated that impaired autonomic function is associated with increased all-cause mortality. Purpose: We hypothesised that ICR would be associated with impaired autonomic function. Methods: After ethical approval and informed consent, consecutive patients attending cardiac rehabilitation in a tertiary referral centre were enrolled. All patients had percutaneous coronary revascularisation. Assessment of autonomic function was performed by determining speed of heart rate recovery between 10 and 20 seconds post orthostatic challenge (HRR10-20). During an active stand, real time heart rate, blood pressure and ECG recordings were taken using non-invasive digital photoplethysmography and HRR10-20 determined. Patients with an rSs >0 were considered incompletely revascularised and those with an rSs of 0 fully revascularised. Demographic data were recorded and statistical analysis performed (SPSS v23). Results: Patients (n=40) comprised those with complete (CR) (n=30) and incomplete (ICR) (n=10) revascularisation. In the ICR group mean rSs was 9. HRR10-20 was impaired in the ICR group (mean -2.9) compared to the CR cohort (mean -5.3) (p=0.001). Completeness of revascularisation was strongly associated with HRR10-20 (Pearson's correlation coefficient 0.529; p≤0.0001). (Figure 1 ) Baseline demographics did not differ significantly. Use of rate limiting medication was similar between cohorts (beta blockers, calcium channel blockers, ivabradine). Conclusions: Our data confirm significant correlation between ICR and impaired autonomic function determined by speed of heart rate recovery. Thus determining autonomic dysfunction post ICR may identify those at increased mortality risk.